MEASUREMENT OF EFFICIENCY UTILIZATION OF OIL PALM SOLID WASTE TO REDUCE FUEL IMPORT LEVELS IN INDONESIA - Hendra, Franka; TH, Estiningsih; Effendi, Riki (Universitas Muhammadiyah Jakarta, 2021)
Indonesia is one of the countries that have a fairly high level of consumption of fuel oil (BBM), based on data from BPH Migas (2018) throughout 2018 which reached 75 million kiloliters or an average of 1.6 million kiloliters per day. The consumption includes 16.2 million kiloliters of certain types of fuel (JBT), special types of fuel for assignment (JBKP), and general types of fuel around 51.3 kiloliters. The data is growing this study aims to measure the efficiency of reducing imports of fuel oil by utilizing solid waste of palm oil and to make proposals for the formulation of planning scenarios to optimize the functions of the Indonesian palm oil downstream industry. This research method combines quantitative and qualitative methods using the concept of efficiency and the Scenario Planning model. The method used in this paper is to calculate the level of efficiency using quantitative data on oil palm based on the amount of plantation area and the solid waste it produces. Then a mapping of the downstream palm oil industry will be carried out by reviewing the results of previous research as well as data and information obtained from accurate sources. The result is that by optimizing the utilization of palm oil solid waste, 7.4 billion liters of bioethanol can be obtained which can be used to produce biofuels to reduce the level of imports of fuel oil in Indonesia.